Why do acute respiratory infections in children remain a pressing problem? Current, prevention and treatment options - E. V. Kanner; A. V. Gorelov; D. V. Pechkurov; M. L. Maksimov; A. S. Ermolayeva (Медицинский совет, 2019)
Literary data on peculiarities of immune system, anti-infectious immunity, including local protection of respiratory tract (lymphaticepithelial pharyngeal system), in children of early and preschool age, causing their higher incidence of acute respiratory infections (ARI) are given in the article. This age period is characterized by «physiological» humoral immune deficiency, reduced activation of the complement system, insufficient synthesis of cytokines, including interferons, T-cell immunosuppression, impaired intercellular cooperation, poor functional activity of natural killers and phagocytes. Despite the large range of means and methods of prophylaxis of infectious and inflammatory diseases of viral and bacterial etiology, it is necessary to search for new approaches taking into account the peculiarities of immune status in young children. The article presents the possibilities of controlling the system of congenital and adaptive immunity with medications, in particular, by using the bacterial lysate Broncho-munal®. The immunoregulatory role of bacterial lysates is presented in detail. The pathogenetic substantiation of the use of bacterial lysate Broncho-munal® for the prevention of acute respiratory infections in children, including children with recurrent respiratory infections is given.